Investigation of different solvents in flexographic printing ink's effects to print quality on coated and uncoated paper - (:unkn) unknown (Chemical Publishing Co., 2011)
There are different solvents used in flexographic inks. There are also different properties of solvents which affect the printing quality in different ways. In this study, seven different flexographic ink with seven different solvents has been prepared. Prepared ink has been printed with IGT F1 Flexo test machine on uncoated and coated papers. The viscosity changes according to the usage of different solvents. This change also affects the printing quality. As a result, the fact that which solvent constitutes the best printing quality for flexographic print on a coated and uncoated paper has been understood.
Keywords: Flexo ink; Flexography; Paper; Print quality; Solvent